The Ethical Treatment of Depression : Autonomy through Psychotherapy - Biegler, Paul, 1963- (Book collections on Project MUSE., 2011)
Is there is a moral imperative on physicians to refer patients with mental depression for psychotherapy rather that treating the ailment with drugs? Psychotherapy, in particular cognitive behavior therapy, promotes autonomy & it is the loss of autonomy, argues Paul Biegler, that is at the heart of depression.